SPGCam: A specifically tailored camera for solar observations - Orozco Suárez, David; Álvarez García, Daniel; López Jiménez, Antonio C.; Balaguer Jiménez, María; Hernández Expósito, David; Labrousse, Pierre; Bailén, Francisco J.; Bustamante Díaz, Isabel; Bailón Martínez, Eduardo; Aparicio del Moral, Beatriz; Morales Fernández, José M.; Sánchez Gómez, Antonio; et al. (Frontiers in Astronomy and Space Sciences, 2023)
Designing a new astronomical instrument typically challenges the available cameras in the3 market. In many cases, no camera can fulfill the requirements of the instrument in terms of4 photon budget, speed, and even interfaces with the rest of the instrument. In this situation, the5 only options are to either downgrade the performance of the instrument or design new cameras6 from scratch, provided it is possible to identify a compliant detector. The latter is the case of7 the SPGCams, the cameras developed to be used with the Tunable Magnetograph (TuMag; Del8 Toro Iniesta et al., 2023) and the Sunrise Chromospheric Infrared spectroPolarimeter (SCIP;9 Katsukawa et al., 2023) for the SUNRISE III mission (Solanki and et al., 2023). SPGCams have10 been designed, developed and built entirely in-house, by the Solar Physics Group (SPG) at the11 Instituto de Astrof ́ısica de Andaluc ́ıa (IAA-CSIC). We report here on the scientific rationale and12 system engineering requirements set by the two instruments that drove the development, as well13 as on the technical details and trade-offs used to fulfill the specifications. The cameras were fully14 verified before the flight, and results from the assembly and verification campaign are presented15 as well. SPGCams share the design, although some parametric features differentiate the visible ones (for TuMag) and the IR ones (for SCIP). Even if they were specifically developed for the17 SUNRISE III mission, the robust and careful design make them suitable for different applications in18 other astronomical instruments.